Relatos sobre inteligência emocional por mulheres líderes - Tomazela, Cleoni Vera (2018)
The issue of gender is increasingly present in the search for understanding and development of a more humanized leadership and administration, in a new organizational dynamic. Women these days achieve positions of leadership that were previously not possible, yet there are several barriers in their career path. The reproduction of gender inequality in organizations finds space in professional environments, because in some organizations when women become leaders, this position is considered an exception. Emotional Intelligence (IE) stands out as a differential in the rise of leadership, be it female or male. One of the ways to define IE and the ability to perceive, evaluate, understand and express emotions and feelings that facilitate thinking, since it promotes emotional and intellectual growth. Another way to characterize IE is to define the leader's ability to manage his / her performance according to his / her self-knowledge, self-control, motivation, empathy and social skills. This work aims to analyze the contribution of emotional intelligence in the performance of women in leadership positions. Data collection was performed through a structured interview. Participants in the survey were women exercising or already exercised leadership roles in large companies in the country. The respondents are part of the Business and Professonal Women (BPW) group, which is an international group with affiliation in 95 countries. It is a group that supports the cause of women in the labor market and has representation in the United Nations United.